A escuta da psicanálise sobre a pele: uma abordage da doença psicossomática - Tereza Cristina Cortes Facury (2011)
The dissertation proposes to put the concept of psychosomatic illness to the test,under the light of Jacques Lacans theoretical reference, privileging the vicissitudes of the articulation between body and language. It aims, thus, to answer how the application of the category of psychosomatic intervenes in order to enforce a unique conception of the relation between symptom and body. It takes, as a starting point, interrogations incited by the clinical practice with children at the João Paulo II Childrens Hospital (FHEMIG), specially of cases treated by dermatology and psychology.To accomplish such goal, we firstly present a census and a revision of the concept of psychosomatic illness, passing through the relations between medicine, psychosomatic and psychoanalysis, privileging the field of dermatology and the attributions related to skin as an exchange organ between interior and exterior. Next, from Jacques Lacans psychoanalytical theory, we detain ourselves in the relation between body and PSP (Psychosomatic Phenomenon), taking the structuring of the body and the incorporation of the structure of language and its effects as fundamental points to be developed. Finally, we investigate what contribution can we extract from Lacans teaching in order to approach the relation between symptom and body in the cases that receive the nomination of psychosomatic. Taking drive as a starting point, represented by the objects gaze and voice, articulated to skin, we study three clinical cases, extracted both from literature and from our own clinical practice.